High-Frequency Vibration Treatment of Human Bone Marrow Stromal Cells Increases Differentiation toward Bone Tissue. (25th March 2013) - Prè, D.; Ceccarelli, G.; Visai, L.; Benedetti, L.; Imbriani, M.; Cusella De Angelis, M. G.; Magenes, G.
Abstract : In order to verify whether differentiation of adult stem cells toward bone tissue is promoted by high-frequency vibration (HFV), bone marrow stromal cells (BMSCs) were mechanically stimulated with HFV (30 Hz) for 45 minutes a day for 21 or 40 days. Cells were seeded in osteogenic medium, which enhances differentiation towards bone tissue. The effects of the mechanical treatment on differentiation were measured by Alizarin Red test, (q) real-time PCR, and protein content of the extracellular matrix. In addition, we analyzed the proliferation rate and apoptosis of BMSC subjected to mechanical stimulation. A strong increase in all parameters characterizing differentiation was observed. Deposition of calcium was almost double in the treated samples; the expression of genes involved in later differentiation was significantly increased and protein content was higher for all osteogenic proteins. Lastly, proliferation results indicated that stimulated BMSCs have a decreased growth rate in comparison with controls, but both treated and untreated cells do not enter the apoptosis process. These findings could reduce the gap between research and clinical application for bone substitutes derived from patient cells by improving the differentiation protocol for autologous cells and a further implant of the bone graft into the patient.